Remote Work Dan Mangement Team Virtual: Pengelolaan Team Yang Tersebar Geografis, Alat Kolaborasi Online, Dan Pengukuran Produktivitas - Arofatus Sakdiah; Farah Anindra Putri; Nurul Septi Amelia; Sinal Sinal; Mochammad Isa Anshori (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Working from home in response to the global pandemic has brought major changes to the world of work. This research aims to see how working from home is implemented and how it affects employee performance. This study shows that employee performance is significantly affected when working from home. One of the perceived benefits is the flexibility of working from home schedules, which allows employees to adjust work schedules to their individual needs. Additionally, there is a positive relationship between employee productivity and a more comfortable work environment with fewer distractions. However, this research also reveals several problems that workers face when working from home. Feelings of social isolation, lack of group collaboration and communication difficulties are some of these problems. Companies must provide adequate technological infrastructure and appropriate training to ensure employees can easily adapt to working from home when faced with these issues. Therefore, the implementation of working from home has a significant impact on employee performance. Benefits such as time flexibility and increased productivity can be achieved, although there are some obstacles that need to be overcome. Therefore, it is important for businesses to continue to monitor and improve work from home practices to optimize employee performance in an ever-changing work environment.